Interaction between cognitive status, fear of falling, and balance in elderly persons - Tavares G.M.S. (2020)
© 2020 CLINICSOBJECTIVE: Evaluate the cognitive function and its relationship with balance, history of falls, and fear of falling in the elderly. METHODS: We evaluated 250 elderly persons aged at least 60 years, who answered a sociodemographic questionnaire about the occurrence of falls in the last year. The cognitive function, balance, and fear of falling were assessed using the Mini-Mental State Examination (MMSE), Berg Balance Scale (BBS), and Falls Efficacy Scale (FES-I) scores, respectively. Participants were allocated into two groups based on the Mini-Mental State Examination (MMSE) score, the Group with Possible Cognitive Decline (GPCD) and the group with no cognitive decline (GNCD). We performed Student's t-test and Pearson's correlation for independent samples. RESULTS: The Group with Possible Cognitive Decline (GPCD) showed lower balance (p=0.003) and greater fear of falling (p=0.008) (BBS=50.98±4.68; FES-I=26.06±8.78) compared to the GNCD (BBS=52.53±3.047; FES-I=23.21±7.74). CONCLUSION: Elderly persons with cognitive decline have lower balance, greater fear of falling, and greater recurrence of falls.